Tata Kelola Kolaboratif dalam Penanganan Permasalahan Anak Pekerja Migran - Koesbardiati, Toetik; Kinasih, Sri Endah; Murti, Delta Bayu; Ida, Rachmah; Wahyudi, Irfan (Universitas Airlangga, 2022)
Abstract The large number of sending migrant workers abroad indicates that the problem of migrant workers in East Java is of course very complex. One of them related to the problem is the children of Indonesian migrant workers (PMI). The problems that arise are vulnerable to the influence of criminality such as brawls, drugs, free sex and pregnancy before marriage. This is why special attention needs to be paid to children whose parents have left them as Indonesian migrant workers (BMI). To respond to this situation, this research is very important with the problems faced by children of migrant workers (APM). Therefore, this study identifies problems faced by children who are abandoned by migrant worker parents, as well as programs that have been developed in Purwodadi village, Donomulyo sub-district, Malang district, one of which is the development of short film production for APM as a vehicle for creativity. and means of communication with parents abroad. The next part of this research is in-depth interviews and observations, whether so far the making of short films can be accessed openly by APM until now. The next stage is to analyze the data that connects the data with the theory used in assessing the responsibilities of surrogate parents, the community and the government in providing protection for children's basic rights in the form of making short films. APM who are members of the community, have collected APM's perception and creativity in terms of survival and child development. For this reason, the production of short films is a collaborative governance program between Non-Governmental Organizations, namely LPKP, the International Labor Organization (ILO) and the United Nations Children's Fund (UNICEF), parents as PMI, APM and village government in this case posyandu cadres. Keywords: children of Indonesian migrant workers, problems of children of migrant workers, collaborative governance Abstrak Banyaknya pengiriman jumlah pekerja migran ke luar negeri menandakan permasalahan pekerja migran di Jawa Timur pun tentunya sangat kompleks. Salah satunya terkait permasalahannya adalah anak pekerja migran indonesia (PMI). Permasalahan yang muncul adalah rentan terhadap pengaruh kriminalitas seperti tawuran, narkoba, seks bebas dan hamil sebelum menikah. Hal inilah perlu adanya perhatian khusus terhadap anak-anak yang ditinggal orang tuanya sebagai buruh migran Indonesia (BMI). Untuk merespon situasi ini maka penelitian ini sangat penting dengan masalah yang dihadapi oleh anak-anak pekerja migran (APM). Oleh karena itu, penelitian ini mengidentifikasi masalah yang dihadapi anak-anak yang ditinggalkan oleh orang tua pekerja migran, serta program-program yang sudah dikembangkan di desa Purwodadi, kecamatan Donomulyo, kabupaten Malang, yang salah satunya pengembangan produksi film pendek bagi APM sebagai wahana kreativitas dan sarana komunikasi dengan orang tua di luar negeri. Bagian selanjutnya dari penelitian ini adalah indepth interview dan observasi, apakah selama ini pembuatan film pendek bisa diakses secara terbuka oleh APM hingga saat ini. Tahap selanjutnya melakukan analisa data yang menghubungkan antara data dengan teori yang digunakan dalam mengkaji pertanggungjawaban orang tua pengganti, masyarakat dan pemerintah dalam memberikan perlindungan terhadap hak-hak dasar anak dalam bentuk pembuatan produksi film pendek. APM yang tergabung dalam komunitas, telah menghimpun persepsi dan kreativitas APM dalam hal kelangsungan hidup dan tumbuh kembang anak. Untuk itu pembuatan produksi film pendek merupakan program collaborative governance antara Lembaga Swadaya Masyarakat yaitu LPKP, International Labour Organisation (ILO) dan United Nations Children's Fund (UNICEF), orang tua sebagai PMI, APM dengan pemerintahan desa dalam hal ini kader posyandu. Kata kunci: anak pekerja migran indonesia, permasalahan anak pekerja migrran, collaborative governance